DESIGN OF A PLANE FIGURE MATHEMATICS EDUCATION GAME FOR CLASS IV STUDENTS BASED ON ANDROID - Heryanto, Deni; Tri Julianto, Indri; Apriliani, Insani; Agreindra Helmiawan, Muhammad (Jurnal Teknik Informatika (Jutif), 2023)
Mathematics is a branch of knowledge related to developing abstract concepts, structures, and relationships in the form of numbers, symbols, and patterns. The issue some students still have trouble recalling formulas, doing division in one of the flat shape materials, and doing multiplication using the formula for the perimeter and area of flat shapes. This research discusses the design of educational games to help fourth-grade students learn flat-shape mathematics. Interviews were conducted with class IV teachers at SDN Sirnajaya Five in conveying material to students; they did not use learning media or visual aids. The problem that often arises is that some students still need help learning flat-shape mathematics. This research aims to build a flat-shape math educational game application for fourth-grade students so that these students can quickly understand the basics of flat-shape material, the definition of flat shapes, formulas, and the properties of flat shapes. The method used is the Multimedia Development Life Cycle (MDLC), a pattern for developing software systems consisting of Concept, Design, Material Collecting, Assembly, Testing, and Distribution stages, which form a workflow for planning and controlling the design of Educational Game applications. This research results in an Android-based flat-shape mathematics educational game application.